Effect of Pre-Grazing Supplementation of Maize Offal and Cowpea Husk on the Performance of Red Sokoto Goats - Yahya M. M; Midau, A.; Hamdalla S; Abdulrahman B.S.; Saidu, M.A. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
This research was conducted at the Livestock Teaching and Research Farm of the Adamawa State University, Mubi.  The essence of the study was to determine the concentrate feed intake and live weight changes of Red Sokoto goats fed cowpea husk and maize offal as well as the nutrient composition of the diets (cowpea husk and maize offal). Twelve Sokoto Red goats were blocked into four treatment groups in a completely randomized designed (RCBD); the supplement concentrate contained Maize offal and cowpea husk (50:50), at graded levels of 0 g (T1), 150 g (T2), 200 g (T3) and 250 g (T4) with T1 as control. The result revealed that feed intake of 143.96, 187.96 and 223.55 g and live weight gain of 26.167, 27.500 and 29.500 g were highly significantly different (P<0.05) among the supplemental groups than those on zero supplementation (T1). Based on the results of this study, goats (Sokoto Red goats) should be supplemented with concentrate (maize offal and cowpea husk) before grazing so as to improve their performance especially during dry season when the forages are insufficient and of very poor quality.